Correlation of fundamental movement skills with health-related fitness elements in children and adolescents: A systematic review - Liu, Cong; Cao, Yuxian; Zhang, Zhijie; Gao, Rong; Qu, Guofeng (Frontiers in Public Health, 2023)
Objective To examine the correlations between fundamental movement skills and health-related fitness elements (cardiopulmonary function, flexibility, body composition, muscle strength and endurance) in children and adolescents and investigate the evaluation methods and tools of fundamental movement skills and health-related fitness. Methods Six electronic databases (Web of Science, PubMed, ProQuest, Scopus, EBSCO and CNKI) were searched, and the research literature on the correlation between children's and adolescents' fundamental movement skills and health-related fitness published since 2002 was collected. The guidelines of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement and the Consolidated Standards of Reporting Trials (CONSORT) statement were used to evaluate the quality of the literature, and the sources, samples, measurement methods, main results and statistical data of the study were analyzed, summarized and discussed. Results After applying the inclusion and exclusion criteria, 49 studies were included. There were 13 tools for evaluating fundamental movement skills and 4 tools for evaluating comprehensive health-related fitness in the included literature. Sufficient research evidence supports a significant positive correlation between fundamental movement skills and cardiopulmonary function (10, 100%) and muscle strength and endurance (12, 100%), and most studies support the positive correlation between fundamental movement skills and flexibility (4, 66.7%), and the significant negative correlation between fundamental movement skills and body composition (29, 67.4%). Studies used skinfold, AF%, BF%, FM, and FFMI as evaluation methods. They showed a consistently significant negative correlation between body composition and fundamental movement skills (9, 100%), while BMI or waist circumference as evaluation methods showed no consistent significant negative correlation result (20, 58.8%). Moreover, in the sub-item evaluation of fundamental movement skills, object manipulation, locomotor and balance skills were all significantly and positively correlated with cardiopulmonary function and muscle strength and endurance. In contrast, locomotor skills were more closely related to body composition than object manipulation skills. Conclusion A significant correlation exists between children's and adolescents' fundamental movement skills and health-related fitness elements.